Designing Enterprise Architecture Using the TOGAF ADM Framework in a Food Manufacturing Company - Andi Naila Quin Azisah Alisyahbana; Sopi; Ukie Tukinah; Matthew Olufemi Adio (Global Research and Collaboration, 2025)
PT. Indofood CBP Sukses Makmur is a leading food manufacturing company in Indonesia, widely recognized for its instant noodle products. In line with rapid technological advancements and the growing complexity of business operations, the integration of information technology (IT) has become a vital necessity for the company. To ensure the effective planning and alignment of IT strategies with business goals, a structured framework is essential. This study aims to design an enterprise architecture for PT. Indofood CBP Sukses Makmur using the TOGAF (The Open Group Architecture Framework) with a focus on the Architecture Development Method (ADM). The research follows several key phases within TOGAF ADM, including Preliminary, Architecture Vision, Business Architecture, Information Systems Architecture, and Technology Architecture. Emphasis is placed on the business architecture phase to capture the core operational processes and strategic needs of the company. The outcome of this research is a tailored enterprise architecture model that enables PT. Indofood CBP Sukses Makmur to optimize its IT resources, support digital transformation initiatives, and align technology deployment with business objectives. The results demonstrate how TOGAF ADM can guide comprehensive enterprise planning, ensure consistency across departments, and provide a clear roadmap for future IT development. Ultimately, the implementation of this model is expected to enhance the efficiency, agility, and competitiveness of PT. Indofood CBP Sukses Makmur within the food manufacturing industry.